Effects of Heat Treatment and Cr Content on the Microstructures, Magnetostriction, and Energy Harvesting Performance of Cr‐Doped Fe–Co Alloys. Issue 5 (24th October 2021) - Nakajima, Kenya; Tanaka, Shota; Mori, Kotaro; Kurita, Hiroki; Narita, Fumio
Abstract : The magnetostrictive effect is one of the most useful properties of ferromagnetic materials. Vibrations in dynamic structures and machines represent a nontraditional alternative energy source, and ferromagnetic materials could potentially convert the kinetic energy of these vibrations into electrical energy using the inverse magnetostrictive effect. Herein, Fe–Co–Cr alloys are fabricated and these materials are applied to vibrational energy harvesting. Specifically, ( Fe 30 Co 70 ) 100 − x Cr x ( x = 0, 0.5, 1.0, or 3.0 at%) alloys are made by arc melting in an argon atmosphere and then heat treated at temperatures that promoted magnetostrictive characteristics. The structural properties of these materials are subsequently investigated using energy‐dispersive X‐ray spectroscopy, while their magnetic properties are assessed with a vibrating sample magnetometer (VSM) and their magnetostrictive characteristics are evaluated with a strain gauge method. Vibrational energy harvesting experiments are conducted and the relationship between the output power and the magnetic/magnetostrictive characteristics of these alloys is examined. The data shows that magnetic permeability is an important factor determining the output power of these Fe–Co alloys, in addition to their magnetostrictive properties. The results provide a basis for the systematic development of magnetostrictive material variants and for new alloys required to meet the needs of future designs. Abstract : Magnetostrictive Fe–Co–Cr alloys with different Cr contents are prepared and the effects of the heat treatment and Cr content conditions on the magnetic and magnetostrictive characteristics of these alloys are evaluated. The results provide a basis for the systematic development of magnetostrictive material variants and for new alloys required to meet the needs of future designs.